Effect of Self-Efficacy on Bedtime Procrastination Among Chinese University Students: A Moderation and Mediation Model - Meng, Xiaolu; Su, Haodong; Li, Chunlu (Frontiers in Psychology, 2022)
Bedtime procrastination (BP) is generally considered to be a maladaptive behavior. However, BP may be an adaptive fast LH strategy within the LH framework; further, personal beliefs about their abilities and resources promote this fast LH strategy. Here, the present study addressed this idea, focusing on the effect of the self-efficacy on BP, the mediation of harm avoidance and the moderation of novelty seeking. Data from 552 Chinese university students (205 male and 347 female) were analyzed using SPSS 25.0 and SPSS PROCESS Macro. Results indicated that harm avoidance partially mediates the relationship between self-efficacy and bedtime procrastination. Main interactional effects have been observed when novelty seeking is introduced in the model as moderator. Implications and limitations of the study and suggestions for further study are discussed.